Konsep Estetika Bentuk Ornamen pada Relief Gunungan Kompleks Pemakaman Raja Cakraningrat IV Kabupaten Bangkalan Madura - Herman Sugianto; Sepbianti Rangga Patriani (Jurnal Kajian dan Penelitian Umum, 2024)
The aim of this research is to determine the aesthetic concept of the form of ornaments found in the reliefs of the Gunungan Raja Cackraningrat IV Bangkalan Madura. Researchers use a qualitative descriptive approach, namely research that is taken from people's opinions and behavior which produces descriptive data in the form of written and spoken words. Qualitative descriptive research does not look for or explain relationships, does not test hypotheses or make predictions but aims to create descriptions that are systematic, factual and accurate. The aesthetic form of relief ornaments in the burial complex of King Cackraningrat IV which is found on the tomb wall consisting of 9 panels in the shape of mountains where the motif used is a form of floral cross-section. Analysis of the aesthetic form of relief on the mountains and namely a combination of two forms of main leaf motifs from two forms of motifs. Different florae undergo stylization to form decorative tendril motifs and mountain motifs. The ornaments used are the type of ornaments that we usually encounter in temples where Hindus worship. Mountains in Hinduism are a symbol of the upper realm, or the sacred place of the gods. The ornaments found on the mountain reliefs at the burial complex of King Cackraningrat IV are also a symbol of harmony that was applied in that era.